Single-layer Ti3C2Tx modification-based GaN / CuO heterostructure NO2 gas sensor

By adopting a single-layer Ti3C2Tx modified GaN/CuO heterostructure in the NO2 gas sensor, the problem of existing NO2 gas sensors working at high temperatures is solved, and the rapid response and high selectivity to NO2 gas under low temperature conditions is achieved, and excellent moisture resistance and stability are achieved.

CN119591146APending Publication Date: 2025-03-11ZHOUKOU NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411758976.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing NO2 gas sensors require high working temperatures, resulting in high cross sensitivity, poor selectivity, low stability and life, complex equipment and high power consumption, pose safety hazards, limiting high-end, intelligent and green applications.

Method used

A single-layer Ti3C2Tx-modified GaN/CuO heterostructure was used to prepare a new gas-sensitive material through hydrothermal reaction, which was used to prepare NO2 gas sensors to achieve rapid response to ultra-trace NO2 gas under low temperature conditions.

Benefits of technology

A high response (37.73) to 100ppm NO2 gas at 60°C, a short response/recovery time (13.7/17s), an ultra-low theoretical detection limit of 49ppt, and exhibits excellent moisture resistance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591146A_ABST
    Figure CN119591146A_ABST
Patent Text Reader

Abstract

The invention discloses a GaN / CuO heterostructure NO2 gas sensor based on single-layer Ti3C2Tx modification, and belongs to the technical field of preparation of gas sensitive materials. The invention firstly discloses a preparation method of a single-layer Ti3C2Tx modified GaN / CuO heterojunction material, and further prepares an NO2 gas sensor (GCT sensor) based on a single-layer Ti3C2Tx modified GaN / CuO heterostructure by taking the prepared heterojunction material as a gas sensitive material, and the sensor can be used for accurately and rapidly detecting ultra-trace NO2 gas in complex environmental pollutants. The response of the developed GCT sensor to 100 ppm NO2 gas at 60 DEG C reaches up to 37.73, the response / recovery time is about 13.7 / 17 s, and the GCT sensor has the ultralow theoretical detection limit of 49 ppt, which is the lowest in all reported NO2 sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas-sensitive material preparation, and specifically relates to a gas-sensitive material based on a single layer of Ti 3 C 2 T x Modified GaN / CuO heterostructure NO 2 Gas sensor. Background Art

[0002] High operating temperature is always NO 2 A problem that cannot be ignored in gas sensors is that high operating temperature makes oxygen ions on the surface of the sensitive layer highly active and can react indiscriminately with various adsorbed gas molecules, resulting in high cross-sensitivity and poor selectivity of the sensor. In addition, high operating temperature reduces the stability and life of the sensor, leading to complex equipment, high power consumption, and safety hazards, which is not conducive to the application and development of high-end, intelligent, and green sensors.

[0003] For example, the Chinese patent document (patent application number 201910268505.9) discloses Au / SnS 2 In order to make nitrogen dioxide gas respond quickly, the operating temperature needs to reach 120℃. 2 Although the gas sensor has the ability to respond quickly, it also needs to work under high temperature conditions and cannot achieve ultra-trace NO under low temperature conditions. 2 Rapid response of gas. Summary of the invention

[0004] The purpose of the present invention is to provide a single-layer Ti 3 C 2 T x Modified GaN / CuO heterostructure NO 2 Gas sensor. Using single layer Ti 3 C 2 T x A new gas-sensitive material was prepared by modifying the GaN / CuO heterojunction. 2 Gas sensor can accurately and rapidly detect ultra-trace NO in complex environmental pollutants 2 Gas, and the response temperature is low.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a single-layer Ti 3 C 2 T x The method for preparing the modified GaN / CuO heterojunction material comprises the following steps:

[0007] Single layer Ti 3 C 2 T x MXene powder, GaN and soluble copper salt are dispersed in water and a single layer of Ti is prepared by hydrothermal reaction. 3 C 2 T x Modified GaN / CuO heterojunction materials.

[0008] Preferably, the single layer Ti 3 C 2 T x MXene powder, GaN and soluble copper salt according to GaN:CuO:Ti 3 C 2 T x =The theoretical weight ratio of 10:1:1 is used for feeding.

[0009] Preferably, the temperature of the hydrothermal reaction is 180-190° C., and the time is 24-25 hours.

[0010] Preferably, the soluble copper salt includes, but is not limited to, one or more of copper acetate, copper chloride and copper nitrate.

[0011] The second technical solution of the present invention is to provide a single layer Ti 3 C 2 T x Monolayer Ti prepared by the preparation method of modified GaN / CuO heterojunction material 3 C 2 T x Modified GaN / CuO heterojunction materials.

[0012] The third technical solution of the present invention is to provide a single layer Ti 3 C 2 T x Modified GaN / CuO heterojunction materials in the preparation of NO 2 Application in gas sensors.

[0013] Technical solution 4 of the present invention: providing a single-layer Ti 3 C 2 T x Modified GaN / CuO heterostructure NO 2 Gas sensor, based on the above single layer Ti 3 C 2 T x The film prepared using the modified GaN / CuO heterojunction material as raw material is a gas-sensitive material.

[0014] The beneficial technical effects of the present invention are as follows:

[0015] At present, GaN-based NO 2 The practical application of gas sensors at lower operating temperatures is still far away, and exploring new methods to activate low-temperature GaN gas sensors for NO 2 The gas sensing properties of gases and their practical applications have always been a hot topic in this field. 3 C 2 T x Modified GaN / CuO heterostructure (GaN / CuO / Ti 3 C 2 T x , GCT)NO 2 Gas sensor for accurate and rapid detection of ultra-trace NO in complex environmental pollutants 2 The developed GCT sensor is effective for 100 ppm NO at 60 °C. 2 The gas response is as high as 37.73, the response / recovery time is about 13.7 / 17s, and it has an ultra-low theoretical detection limit of 49ppt, which is the lowest among all reported NO 2 The GCT sensor exhibits excellent moisture resistance and can maintain 81% of its initial response even at 85% relative humidity, which proves its stability and reliability under complex environmental conditions. In addition, the present invention also proposes a "humidity compensation method", which indicates that a 1% decrease in relative humidity is equivalent to 66.13 ppb NO 2 The influence of water molecules on the resistance of GCT sensors provides a solution to eliminate the influence of water molecules on the gas-sensitive performance of sensors in complex environments. Finally, the sensing mechanism of the improvement and decline of the gas-sensitive performance of sensors under low / high relative humidity conditions is fully explained. 2 It lays an important foundation for the application of gas sensors in actual complex environment monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a flow chart of preparing a GCT sensor according to Example 1 of the present invention.

[0017] Figure 2 The XRD patterns of GCT, GC and GT prepared in Example 1 and Comparative Examples 2-3 are shown.

[0018] Figure 3 SEM images of GaN, GC, GT and GCT prepared in Comparative Examples 1 to 3 and Example 1, and an EDX spectrum of GCT prepared in Example 1, wherein (a) is the SEM image of GaN, (b) is the SEM image of GC, (c) is the SEM image of GT, (d) is the SEM image of GCT, and (e) to (l) are EDX spectra of GCT.

[0019] Figure 4 TEM and HRTEM images of GaN, GC, GT and GCT prepared in Comparative Examples 1 to 3 and Example 1, wherein (a) is a TEM image of GaN, (b) is a HRTEM image of GaN, (c) is a TEM image of GC, (d) is a HRTEM image of GC, (e) is a TEM image of GT, (f) is a HRTEM image of GT, (g) is a TEM image of GCT, and (h) is a HRTEM image of GCT.

[0020] Figure 5 XPS spectra of GCT, GaN, GC and GT prepared in Example 1 and Comparative Examples 1 to 3, wherein (a) is the Ga 2p spectrum of GCT and GaN, (b) is the N1s spectrum of GCT and GaN, (c) is the Cu 2p spectrum of GCT and GC, (d) is the O1s spectrum of GC and GaN, (e) is the Ti 2p spectrum of GCT and GT, and (f) is the C1s spectrum of GCT and GT.

[0021] Figure 6 The N of the GaN gas-sensitive film and the GCT gas-sensitive film prepared according to the method of Comparative Example 1 and Example 1 is 2 Adsorption-desorption isotherms, where (a) is the GaN gas sensitive film N 2 Adsorption-desorption isotherms, (b) N of GCT gas sensitive film 2 Adsorption–desorption isotherms.

[0022] Figure 7 The sensors prepared in Comparative Examples 1 to 3 and Example 1 reacted with 100 ppm NO at different temperatures. 2 The response value (a) of the Gan sensor to different concentrations of NO at the optimal working temperature 2 The resistance (b) and response value (c) curves of the GC sensor at the optimal working temperature for different concentrations of NO 2 The resistance (d) and response value (e) curves of the GT sensor at the optimal working temperature for different concentrations of NO 2 The resistance (g) and response value (h) curves of the GCT sensor at the optimal working temperature for different concentrations of NO 2 The resistance (i) and response value (j) of each sensor 2 Fitting curves of concentration versus response value (k) and (l) and the average response and recovery time (m) of each sensor at the optimal working temperature.

[0023] Figure 8The selectivity of each sensor prepared in Example 1 and Comparative Examples 1 to 3 to 100 ppm of various interfering gases at the optimal working temperature (a), the response change curve of the GCT sensor to 100 ppm of various interfering gases (b), and the selectivity of each sensor to 100 ppm NO 2 Repeatability (c) and GCT sensor at 100ppmNO 2 Long-term stability in (d).

[0024] Fig. 9 (a) is a curve of normalized baseline resistance and response value of the GCT sensor prepared in Example 1 at different relative humidities at 60° C., and (b) is a curve of change of response value at different relative humidities over time.

[0025] Fig.10 GCT sensor for NO at 60°C 2 Schematic diagram of gas sensing mechanism. DETAILED DESCRIPTION

[0026] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0027] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0028] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0029] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0030] The test environment of the gas test involved in the present invention is a dust-free laboratory with a constant temperature of 23-25°C and a relative humidity (RH) of 40%. The gases tested were purchased from Nanjing Hongfeng Gas Co., Ltd. and were measured by weighing method (using pure air (79% N 2 +21% O 2The concentration of the gas to be measured is modulated by the MF2400 gas dilution device. Specifically, the raw gas of known concentration is carefully weighed and mixed according to the calculated mixing ratio. Then, the target gas concentration is verified and stored under appropriate conditions. In addition, NH 3 The gas is dry without water vapor. The electrical characteristics of the sensor are recorded using a Keithley 2400 source meter. In addition, the response value of the sensor is represented by S, which is defined as the change in sensor resistance. The calculation formula is shown in formula (1):

[0031]

[0032] Among them, R air Represents the initial resistance value of the sensor in air, R gas Indicates the resistance value of the sensor in the presence of the target gas. In addition, the response and recovery time is defined as the time required for the sensor to reach 90% of its equilibrium resistance value.

[0033] Example 1

[0034] Preparation of GCT sensor:

[0035] (1) Single-layer Ti 3 C 2 T x Preparation of MXene powder: 10gTi 3 AlC 2 The powder was added to 80 mL of HF (concentration ≥ 40 wt.%) aqueous solution, stirred at room temperature for 24 h, and centrifuged at 10,000 rpm for 10 min to separate the precipitate from the mixed solution. The precipitate was then washed with deionized water and anhydrous ethanol several times to remove residual HF and impurities until the pH reached about 6. 3 C 2 T x Dispersed in deionized water, ultrasonically treated for 6 h, and the upper layer solution was collected by high-speed centrifugation to obtain a monolayer Ti 3 C 2 T x Finally, it was dried in an oven at 90 °C for 24 h to obtain a single layer of Ti 3 C 2 T x MXene powder for subsequent use.

[0036] (2) Single-layer Ti 3 C 2 T x Preparation of modified GaN / CuO heterojunction materials: First, 0.5 g GaCl 31g urea was dissolved in 21mL trioctylamine (TOA) solution and stirred with a magnetic stirrer for 2h. The mixed solution was then poured into a polytetrafluoroethylene autoclave and reacted at 120℃ for 12h. After the reaction, the filtered product was annealed in an ammonia tube furnace at 850℃ for 1h to obtain GaN. Subsequently, the prepared single layer Ti 3 C 2 T x MXene powder is dispersed together with GaN in a copper acetate aqueous solution (ensuring the theoretical weight ratio of GaN:CuO:Ti 3 C 2 T x =10:1:1), stirred for 2 hours to completely dissolve. Then the mixed solution was reintroduced into the autoclave and reacted at 180°C for another 24 hours, and then filtered to obtain a single layer of Ti 3 C 2 T x Modified GaN / CuO heterojunction material (i.e. GaN / CuO / Ti 3 C 2 T x Composite material, denoted as GCT).

[0037] (3)GaN / CuO / Ti 3 C 2 T x Preparation of gas sensor: 0.05 g of prepared GCT sample was dissolved in 1 mL of anhydrous ethanol and ultrasonicated for 2 h. Then 0.5 mL of the dispersion was drop-casted evenly onto a 10.0 mm × 10.0 mm × 1.0 mm SiO2 substrate with Au / Cr interdigital electrodes using a pipette. 2 / Si substrate. Subsequently, the assembly was placed on a hot plate and heated at 100°C for 1 hour to form a gas-sensitive film, and the GCT sensor was successfully prepared.

[0038] Example 1: Flow chart of preparing GCT sensor Figure 1 .

[0039] Comparative Example 1

[0040] Preparation of GaN sensor:

[0041] Compared with the preparation steps of the GCT sensor in Example 1, the differences are as follows: the preparation of the gas sensitive film uses GaN of equal mass to replace GCT; the preparation steps of GaN are the same as those in Example 1.

[0042] Comparative Example 2

[0043] Preparation of GC sensor:

[0044] Compared with the preparation steps of the GCT sensor in Example 1, the difference is that the preparation of the gas sensitive film uses an equal mass of GaN / CuO composite material (GC) to replace GCT; the preparation of GC is different from that of GCT in Example 1: the single layer of Ti 3 C 2 T x Addition of MXene powder.

[0045] Comparative Example 3

[0046] Preparation of GT sensor:

[0047] Compared with the GCT sensor preparation steps of Example 1, the difference is that the preparation of the gas sensitive film uses GaN / Ti with equal mass. 3 C 2 T x The composite material (GT) replaces GCT; the preparation of GT is different from that of GCT in Example 1, except that the addition of copper acetate is omitted.

[0048] The XRD patterns of GCT, GC and GT prepared in Example 1 and Comparative Examples 2 to 3 are shown in Figure 2 .

[0049] Figure 2 The diffraction pattern shows that the peaks at 2θ=32.4°, 34.6°, 36.8°, 48.1°, 57.8°, 63.5°, 67.8°, 69.1° and 70.5° are consistent with the (100), (002), (101), (102), (110), (103), (112), (200) and (201) crystal planes in GaN. The peaks appearing at 2θ=32.5°, 35.6°, 38.8°, 48.7°, 53.6°, 58.3°, 61.7°, 66.2° and 68.1° correspond to the (110), (11-1), (111), (20-2), (020), (202), (11-3), (31-3) and (113) crystal planes of CuO. In addition, the characteristic peaks observed at 2θ = 6.5°, 16.7°, 26.4°, and 60.7° are attributed to Ti 3 C 2 T x (002), (004), (006) and (110) planes. In GCT-based composites, CuO and Ti 3 C 2 T x The diffraction peaks of CuO and Ti in the composite material are not obvious. 3 C 2 T x The concentration of GaN is low and their diffraction peaks overlap with the diffraction peaks of the original GaN material.

[0050] The SEM images of GaN, GC, GT and GCT prepared in Comparative Examples 1 to 3 and Example 1 and the EDX spectrum of GCT prepared in Example 1 are shown in FIG. Figure 3 , where (a) is the SEM image of GaN, (b) is the SEM image of GC, (c) is the SEM image of GT, (d) is the SEM image of GCT, and (e) to (l) are EDX spectra of GCT.

[0051] Figure 3 As shown in (a) to (d), GaN presents an irregular micron-sized block morphology, while CuO appears as nano-spherical particles with a diameter of about 20 to 30 nm. 3 C 2 T x It presents a single-layer lamellar structure. Figure 3 (e) to (l) show that the EDX of the GCT composite material confirms the presence of Ga, N, Cu, O, Ti, C and F elements, confirming the successful preparation of the GCT composite material. The trace amount of F element detected in the GCT can be attributed to the residue of the HF etching process.

[0052] TEM and HRTEM images of GaN, GC, GT and GCT prepared in Comparative Examples 1 to 3 and Example 1 are shown in Figure 4 , where (a) is the TEM image of GaN, (b) is the HRTEM image of GaN, (c) is the TEM image of GC, (d) is the HRTEM image of GC, (e) is the TEM image of GT, (f) is the HRTEM image of GT, (g) is the TEM image of GCT, and (h) is the HRTEM image of GCT.

[0053] Figure 4 (a) to (g) show TEM and high-resolution TEM (HR-TEM) images of GaN, GC, GT, and GCT composites. The lattice fringes with a width of 0.27 nm in GaN correspond to the (100) crystal plane of GaN, the interplanar spacing of 0.26 nm in CuO is attributed to the (006) crystal plane of CuO, and the interplanar spacing of 0.26 nm in CuO is attributed to the (006) crystal plane of CuO. 3 C 2 T x The lattice fringe width is 0.23nm, which is similar to Ti 3 C 2 T x In addition, Figure 4 As shown in (g) to (h), GaN and CuO are evenly dispersed in Ti 3 C 2 T x Nanosheet surface, while the single layer Ti 3 C 2 T xThe sheet structure is more conducive to the adsorption / desorption of gases by the composite material, thereby enhancing the gas sensing performance.

[0054] The XPS spectra of GCT, GaN, GC and GT prepared in Example 1 and Comparative Examples 1 to 3 are shown in Figure 5 , where (a) is the Ga 2p spectrum of GCT and GaN, (b) is the N1s spectrum of GCT and GaN, (c) is the Cu 2p spectrum of GCT and GC, (d) is the O1s spectrum of GC and GaN, (e) is the Ti 2p spectrum of GCT and GT, and (f) is the C1s spectrum of GCT and GT.

[0055] X-ray photoelectron spectroscopy (XPS) was used to further investigate the chemical state of the material. Figure 5 As shown in (a), the binding energy peaks are 21.41eV / 21.37eV and 19.86eV / 20.42eV, corresponding to the Ga-N and Ga-O bonds in GaN and GCT, respectively. Figure 5 As shown in (b), the N 1s peaks are located at 396.99 eV / 397.53 eV and 393.90 eV / 394.89 eV, corresponding to the N-Ga and Ga-LMM bonds in GaN and GCT, respectively. Figure 5 The binding energy peaks of 933.37eV / 933.05eV and 953.32eV / 953.01eV in (c) belong to the Cu 2p3 / 2 and Cu 2p1 / 2 states of GaN and GCT, respectively. 2+ The paramagnetic satellite peaks. Figure 5 As shown in (d), the peaks of O 1s at 532.78 eV, 531.38 eV, and 529.38 eV correspond to OH - , O 2- and O2 - For GCT, Ti 3 C 2 T x The introduction of leads to the formation of Ti-OH and C-OH bonds, which are abundant active sites and enhance the gas sensing properties of the material. Figure 5 As shown in (e), the fitted peaks of the Ti 2p spectrum at 453.97eV and 460.49eV, 454.116eV and 460.297eV, 455.071eV and 461.811eV, 455.448eV and 462.00eV, 458.08eV and 463.934eV, 457.891eV and 463.594eV correspond to TiO in GT and GCT, respectively. 2 , Ti-C, Ti-X bonds. In addition, the C1s spectra of GT and GCT are as follows Figure 5As shown in (f), the peak values ​​are 280.88eV / 281.068eV, 284.8eV / 284.4eV, 286.65eV / 287.246eV and 288.681eV / 288.525eV, which are attributed to C-Ti, CC, CN and CO bonds in GT and GCT, respectively.

[0056] In order to further characterize the gas-sensitive film, N 2 The specific surface area and pore size distribution of the GaN gas-sensitive film and the GCT gas-sensitive film prepared according to the method of Comparative Example 1 and Example 1 were measured by adsorption-desorption isotherms. 2 Adsorption-desorption isotherms are shown in Figure 6 , where (a) is GaN gas-sensitive film N 2 Adsorption-desorption isotherms, (b) N of GCT gas sensitive film 2 Adsorption–desorption isotherms.

[0057] like Figure 6 As shown in Figure 2, the isotherms of GaN and GCT are both type IV with obvious hysteresis loops. BET analysis shows that the specific surface areas of GaN and GCT are 9.37 m 2 / g and 70.89m 2 The significant increase in the specific surface area of ​​GCT may be due to the modification of smaller-sized CuO and layered Ti 3 C 2 T x The contribution of the larger surface area of ​​the structure. The increased surface area is more conducive to the adsorption / desorption of gas molecules, thereby improving the gas sensing performance of the material.

[0058] The sensors prepared in Comparative Examples 1 to 3 and Example 1 reacted with 100 ppm NO at different temperatures. 2 The response value (a) of the Gan sensor to different concentrations of NO at the optimal working temperature 2 The resistance (b) and response value (c) curves of the GC sensor at the optimal working temperature for different concentrations of NO 2 The resistance (d) and response value (e) curves of the GT sensor at the optimal working temperature for different concentrations of NO 2 The resistance (g) and response value (h) curves of the GCT sensor at the optimal working temperature for different concentrations of NO 2 The resistance (i) and response value (j) of each sensor 2 The fitting curves of concentration and response value (k) and (l) as well as the average response and recovery time (m) of each sensor at the optimal working temperature are shown in Figure 7 .

[0059] like Figure 7As shown in (a), the effect of operating temperature on the gas sensing performance of the sensor was studied. Four different sensors (GaN, GC, GT and GCT) were evaluated for 100 ppm NO at different operating temperatures. 2 Obviously, each sensor exhibits a 2 The optimal operating temperature at which the response reaches the peak. Specifically, the GaN sensor exhibited the highest response (2.83) at 180°C, while the GT sensor reached the peak at 90°C (3.66). The GC sensor had an optimal temperature of 120°C (6.41), while the GCT sensor achieved the maximum response (37.73) at a lower temperature of 60°C. These data indicate that the GCT sensor can achieve high response at lower temperatures, with potential advantages in terms of energy saving and cost effectiveness. The four sensors responded to different NO 2 The concentration response resistance and response curve are as follows Figure 7 As shown in (b) to (j), it can be seen that as NO 2 With the increase of NO concentration, the resistance / response of all sensors increased, showing the typical response behavior of n-type gas sensitive materials. 2 The response of the GCT sensor to 100 ppm NO at 60 °C was significantly better than that of the other three sensors. 2 The response of the GaN sensor at 180°C is 13.35 times higher than that of the GaN sensor at 180°C, which significantly improves the sensitivity of the GaN sensor to NO 2 The response concentration fitting curves of the four sensors are shown in Figure 7 As shown in (k) and (l), the equation in (k) is as follows:

[0060] GaN:y 1 =1.23x 1 0.17 R 2 =0.93;

[0061] GT:y 2 =1.20x 2 0.22 R 2 =0.91;

[0062] GC:y 3 =1.15x 3 0.36 R 2 =0.96;

[0063] GCT:y 4 =2.93x 4 0.55 R 2 =0.99.

[0064] Among them, y is the response and x is NO 2 Concentration, R 2 is the coefficient of determination. In addition, the sensor exhibited a highly linear relationship between response and concentration, and the theoretical detection limit of each sensor was calculated as follows

[0065] GaN:

[0066] GT:

[0067] GC:

[0068] GCT:

[0069] like Figure 7 The figure (m) shows the detection of 100ppm NO by four sensors at their respective optimal working temperatures. 2 It can be seen that the average response / recovery time of the GCT sensor is the shortest (13.7 / 17s), indicating that the GCT sensor is more effective in detecting NO 2 The post-reaction is rapid, returning to the initial state quickly after the gas concentration decreases, which is crucial for real-time monitoring and rapid response to environmental changes.

[0070] The selectivity of each sensor prepared in Example 1 and Comparative Examples 1 to 3 to 100 ppm of various interfering gases at the optimal working temperature (a), the response change curve of the GCT sensor to 100 ppm of various interfering gases (b), and the selectivity of each sensor to 100 ppm NO 2 Repeatability (c) and GCT sensor at 100ppm NO 2 Long-term stability (d) Figure 8 .

[0071] Figure 8 (a) compares the performance of each sensor at the optimal operating temperature for six different harmful gases (NO 2 NH 3 , H 2 , CO, SO 2 , H 2 The results show that the GCT sensor responds to NO 2 The GCT sensor has the highest response to NO 2 The selectivity of GCT is higher (the response curves of GCT to the other five gases are as follows Figure 8 (b)), confirming its 2 Potential for detection. Figure 8 (c) shows the sensor under the best working temperature and 100ppm NO2 From the repeatability test curve under gas conditions, it can be seen that under the respective test conditions, the baseline resistance and saturation resistance of all sensors have minimal fluctuations and have good repeatability. Figure 8 (d) shows the change in responsiveness of the GCT sensor during the long-term stability test, indicating that the GCT sensor exhibited excellent long-term stability throughout the 6-week test, and its responsiveness and resistance value changes were within a controllable range, which is crucial to the reliability and durability of the sensor in practical applications.

[0072] The normalized baseline resistance and response value curve of the GCT sensor prepared in Example 1 at different relative humidity at 60°C (a) and the response value change curve of different relative humidity over time (b) are shown in FIG. Fig. 9 .

[0073] Humidity is a key environmental factor affecting the performance of gas sensors because it can change the surface properties and conductivity of the sensor material. Fig. 9 (a) describes in detail the response and resistance changes of the GCT sensor under different relative humidity conditions. Fig. 9 (b) shows the response curve of the GCT sensor at different humidity levels over time. At the same time, it is calculated that a 1% decrease in relative humidity is equivalent to 66.13 ppb NO 2 Effect on the resistance of GCT sensor. As the relative humidity increases from 40% to 85%, the responsivity / resistance of the GCT sensor shows a clear downward trend. However, even at 85% RH, the GCT sensor can still maintain 81% of its initial responsivity (30.56), indicating that the sensor still has a strong detection ability for the target gas in a high humidity environment. This trend can be explained by two main mechanisms. First, in a high humidity environment, water vapor molecules easily form a water film on the surface of the sensor's sensitive layer, which not only occupies the active sites originally used for gas molecule adsorption, but also may change the surface properties of the sensitive layer. This physical adsorption effect reduces the effective adsorption area of ​​the sensor for target gas molecules, thereby affecting its response performance. Secondly, the accumulation of water molecules on the surface of the sensitive layer forms a physical barrier, which hinders the full contact between oxygen molecules and the surface of the sensitive layer, because the formation of oxygen ions on the sensor surface blocks the redox reaction on the sensor surface, and this barrier reduces the gas-sensing performance of the sensor.

[0074] GCT sensor for NO at 60℃ 2 Schematic diagram of gas sensing mechanism Fig.10 .

[0075] In order to further clarify the sensing mechanism of GCT composite materials, its band structure and surface reaction were studied. As a resistive gas sensor, the response of the sensor is manifested as a change in sensor resistance, which is closely related to the band structure and surface reaction of the material. Fig.10 As shown, the Fermi level difference between GaN (4.2eV) and CuO (5.3eV) causes electrons to transfer from the lower Fermi level of GaN to the higher Fermi level of CuO upon contact to balance the electron distribution across the interface. This electron transfer leads to the formation of an electron depletion layer on the GaN side and the accumulation of electrons on the CuO side. The generation of this built-in electric field promotes the separation of carriers and enhances the material's response to gas molecules. The sensing mechanism of the GCT sensor is intricately linked to the surface reactions that occur when exposed to air and nitrogen dioxide. Initially, oxygen molecules from the air are physically adsorbed to the sensor surface and converted to O 2(ads) (Equation 2). Subsequently, electrons are obtained from the conduction band of the semiconductor to form negatively charged oxygen ions In the presence of oxygen vacancies, further reduction can occur, forming The above process depletes the electrons in the GCT, further enhancing the formation of the depletion layer and thus increasing the resistance of the sensor. 2 In this environment, the surface reaction mechanism of the GCT sensor is as follows: Initially, gaseous NO 2 The molecules are physically adsorbed to the sensor surface to form adsorbed NO 2(ads) (Equation 5). These molecules capture electrons from the conduction band of the semiconductor and convert them into negatively charged ions. Then, NO 2(ads) Oxygen ions adsorbed on the surface reacts with the additional electrons to produce an increased concentration of Negatively charged and Can interact with electrons to regenerate gaseous NO 2(gas) and releases the adsorbed oxygen ions In addition, NO 2(ads) The molecule can be and an electron to form This further consumes electrons and causes the width of the depletion layer to increase, which in turn causes a further increase in the sensor resistance.

[0076] O 2(gas) →O 2(ads) (2)

[0077]

[0078] NO 2(gas) →NO 2(ads) (5)

[0079]

[0080] Ti 3 C 2 T x The modification of Ti introduces additional electron transfer channels and gas adsorption sites. 3 C 2 T x The conductivity of the heterostructure facilitates the transfer of electrons within the heterostructure, while its surface functional groups enhance the transfer of NO 2 The chemical adsorption of Ti molecules improves the sensitivity and response speed of the sensor. 3 C 2 T x The large surface area provides abundant adsorption sites for gas molecules, which is beneficial for their interaction with GaN and CuO, thereby enhancing the response of the sensor.

[0081] H 2 O+e - +*=H * +OH - (10)

[0082] OH - +h + →OH (11)

[0083]

[0084] NO 2 +OH→HNO 3(gas) (13)

[0085]

[0086] However, due to the surface free radicals generated by the splitting of water molecules adsorbed on the surface of the material (Equation 10-13), the sensor still exhibits NO at low relative humidity. 2 Specifically, the material dissociates water molecules under an external bias voltage of 0.1 V to form surface hydroxyl groups (OH - ) and H * The OH formed - will capture a hole (h + ) to form OH radicals, and the adsorbed oxygen molecules will also react with H * The reaction forms hydrogen ions (H + ) and superoxide radicals When exposed to NO 2 When in the gas, the adsorbed NO 2(ads ) reacts with OH radicals to generate gaseous HNO 3(Equation 14). Under an external bias voltage of 0.1 V, the electrons generated by ·OH are transferred to the positive electrode. In addition, the adsorbed NO 2(ads) The molecule can also react with H + and Formation of gaseous HNO 3 (Equation 15). Therefore, the above reaction will also consume additional electrons, significantly increasing the sensor resistance value, showing NO 2 However, at higher relative humidity, the sensor showed reduced NO 2 Sensor response (such as Fig. 9 As shown in (a), excess water molecules will occupy the surface of the material. 2 and NO 2 The surface active sites of the molecules hinder the O 2 and NO 2 The further adsorption of molecules will have an adverse effect on the gas sensing performance. Most importantly, these reaction processes always occur competitively at each relative humidity to create a dynamic equilibrium. However, when the relative humidity increases, the equilibrium state will be destroyed, and a new dynamic equilibrium will be formed again between surface activation and excess water molecule adsorption, resulting in NO 2 Therefore, the interference of water molecule adsorption causes the sensor signal to be severely attenuated. In addition, Ti 3 C 2 T x It helps to maintain the stability of the sensor in a high humidity environment and reduce the negative impact of humidity on sensor performance. In summary, the band structure and interface effect of the GCT ternary composite material work together to achieve NO 2 Efficient detection of gases. This material design not only provides a new strategy for the development of high-performance gas sensors, but also shows potential application prospects in environmental monitoring and other related fields.

[0087] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A single-layer Ti3C2T x A method for preparing a modified GaN / CuO heterojunction material, characterized in that: The following steps are involved: Single layer Ti3C2T x MXene powder, GaN and soluble copper salt were co-dispersed in water, and a single-layer Ti3C2T3 was prepared by hydrothermal reaction. x Modified GaN / CuO heterojunction materials.

2. The single-layer Ti3C2T according to claim 1 x A method for preparing a modified GaN / CuO heterojunction material, characterized in that: The single-layer Ti3C2T x MXene powder, GaN and soluble copper salt according to GaN:CuO:Ti3C2T x =The theoretical weight ratio of 10:1:1 is used for feeding.

3. The single-layer Ti3C2T according to claim 1 x A method for preparing a modified GaN / CuO heterojunction material, characterized in that: The temperature of the hydrothermal reaction is 180-190° C. and the time is 24-25 hours.

4. The single-layer Ti3C2T according to claim 1 x A method for preparing a modified GaN / CuO heterojunction material, characterized in that: The soluble copper salt includes one or more of copper acetate, copper chloride and copper nitrate.

5. A single-layer Ti3C2T3 according to any one of claims 1 to 4 x Monolayer Ti3C2T prepared by the preparation method of modified GaN / CuO heterojunction material x Modified GaN / CuO heterojunction materials.

6. A single-layer Ti3C2T3 as claimed in claim 5 x Application of modified GaN / CuO heterojunction materials in the preparation of NO2 gas sensors.

7. A method based on single-layer Ti3C2T x The modified GaN / CuO heterostructure NO2 gas sensor is characterized by: The single-layer Ti3C2T x The film prepared using the modified GaN / CuO heterojunction material as raw material is a gas-sensitive material.

Citation Information

Patent Citations

  • Au / SnS2 nitrogen dioxide gas sensor and preparation process and application thereof

    CN110095506A